The Influence of A Cooperative Learning Model of Team Games Tournament (TGT) Type on Mathematic Critical Thinking Ability through A Scientific Approach to Statistical Materials - Wati, Dita Fitria; Ilmayasinta, Nur; Prafianti, Rayinda Aseti (Universitas Muhammadiyah Surakarta, 2024)
This research was conducted on class This study is quantitative research. The data obtained in this research is from the initial test (pretest) and final test (posttest) by taking samples from class X3 as the experimental class and X5 as the control class. The data analysis techniques used are normality test, homogeneity test and hypothesis test. In the decision making criteria for the Mann Whitney U-Test, it is said that if the value of Asymp.Sig. (2-tailed) < 0.05 then